Grain supply and policy developments - International Food Policy Research Institute (International Food Policy Research Institute, 1976)
Notwithstanding record production in India and other developing market economies, world grain supplies remain tight largely because of poor crops in the USSR and Eastern and Western Europe. Grain stocks may rise slightly in the USA and in some Asian countries, but total world stocks remain at very low levels. In the absence of stocks, world food supplies for 1976/77 are again largely dependent on current output. Despite the absence of significant growth in total world output, the production increases in many developing countries and North American have resulted in lower farm prices in many countries. Export prices of some grains, fertilizers, and shipping all have declined, reducing the burden of these items on food deficit developing countries. Even so, the dependence of developing countries upon grain imports remains high; and unless there is a market rise in the rate of growth of food production, the dependency is likely to increase.